Development and Verification of Glutamatergic Synapse-Associated Prognosis Signature for Lower-Grade Gliomas - Ye, Liguo; Xu, Yang; Hu, Ping; Wang, Long; Yang, Ji’an; Yuan, Fan’en; Wang, Yixuan; Zhang, Chunyu; Tian, Daofeng; Chen, Qianxue (Frontiers in Molecular Neuroscience, 2021)
Background: Lower-grade glioma (LGG) is the most common histology identified in gliomas, a heterogeneous tumor that may develop into high-grade malignant glioma that seriously shortens patient survival time. Recent studies reported that glutamatergic synapses might play an essential role in the progress of gliomas. However, the role of glutamatergic synapses related biomarkers in LGG has not been systemic researched yet. Methods: The mRNA expression data of glioma and normal brain tissue were obtained from The Cancer Genome Atlas database and Genotype-Tissue Expression, respectively, and the Chinese Glioma Genome Atlas database was used as a validation set. Difference analysis was performed to evaluate the expression pattern of glutamatergic synapses-related genes (GSRGs) in LGG. The least absolute shrinkage and selection operator (LASSO) Cox regression was applied to construct the risk signature (GSRS), and the risk score of each LGG sample was calculated based on the coefﬁcients and expression value of selected GSRGs. Univariate and multivariate Cox regression analyses were used to investigate the prognostic value of risk score. Immunity and single-sample gene set enrichment analysis (ssGSEA) was performed to explore the association between risk score and the characters of tumor microenvironment in LGG. Gene set variation analysis (GSVA) was performed to investigate the potential pathways related to GSRS. The HPA database and real-time PCR were used to identify the expression of hub genes identified in GSRS. Results: A total of 22 genes of 39 GSRGs were found differentially expressed among normal and LGG samples. Through LASSO algorithm, 14-genes GSRS constructed was associated with the prognosis and clinicopathological features of patients with LGG. Further, the risk score level was significantly positively correlated to the infiltrating level of immunosuppressive cells, including M2 macrophages and regulatory T cells. GSVA identified a series of cancer-related pathways related to GSRS, such as P13K-AKT and P53 pathways. Moreover, ATAD1, NLGN2, OXTR, and TNR, hub genes identified in GSRS, were considered as potential prognostic biomarkers in LGG. Conclusion: A 14-genes glutamatergic synapses-related risk signature was constructed and verified in this study. We provided a novel insight into the role of GSRS in LGG through a series of bioinformatics methods.